Program Pengembangan Usaha Kecil pada Sentra Industri Kecil Handycraft di Desa Tutul Kecamatan Balung Kabupaten Jember (Small Business Development Programs on the Center of Handicraft Small Industry in Tutul Village, Balung Sub-ditsrict, Jember Regency) - Ghaisani, Oktavia Nabilah; Azhari, A Kholiq; Rohman, Hermanto (University of Jember, 2019)
AbstractStarting from the existing problems related to human resources where the majority of the people of TutulVillage have a low educational background. Although in making handicrafts, formal education is not veryimportant, the low quality of the human resources is not supported by the development programs of skillstraining. The second problem is that small handicraft industry businessmen in Tutul village are stillconstrained by financial or capital resources, and the marketing process is still conventional, so the amountof production is still based on the number of orders coming. Therefore, this research aims to describe theimplementation of small business development programs in the center of handicraft small industry in Tutulvillage.This descriptive research employed a qualitative approach. The research data were collected throughobservation, documentation, and interview. The village head as themain informant was determined by usingsnowball sampling technique. To test thedata validity, the researchers conducted perseverance ofobservation and data triangulation. Data were analyzedby using qualitative data analysis by Miles andHuberman, namely data reduction, data presentation, and drawing conclusion. The findings indicated thatthe small business development programs in the center of handicraft small industry in Tutul village werethedevelopment programs of managerial aspect, especially human resource skills and marketing. The second,capital development programwas carried out by providing capital assistance to craftsmen by PT TelkomJember. The next program was through a partnership program that aimed to expand the network ofcraftsmen. The fourth program was the development of the center of small industry under the auspices ofTechnical Implementation Unit of Job Training Center (UPT BLK)Jember. The last development programwas coaching carried out by PT Telkom and UPT BLK Jember by conducting training and the assistance offacilities and infrastructures.Keywords: program, development, and small industry